Examining the Role of the Noradrenergic Locus Coeruleus for Predicting Attention and Brain Maintenance in Healthy Old Age and Disease: An MRI Structural Study for the Alzheimer's Disease Neuroimaging Initiative. - Dockree, Paul; Robertson, Ian; Whelan, Robert; Kenny, Rose (My University, 2021)
The noradrenergic theory of Cognitive Reserve (Robertson, 2013-2014) postulates that the upregulation of the locus coeruleus-noradrenergic system (LC-NA) originating in the brainstem might facilitate cortical networks involved in attention, and protracted activation of this system throughout the lifespan may enhance cognitive stimulation contributing to reserve. To test the above-mentioned theory, a study was conducted on a sample of 686 participants (395 controls, 156 mild cognitive impairment, 135 Alzheimer's disease) investigating the relationship between LC volume, attentional performance and a biological index of brain maintenance (BrainPAD-an objective measure, which compares an individual's structural brain health, reflected by their voxel-wise grey matter density, to the state typically expected at that individual's age). Further analyses were carried out on reserve indices including education and occupational attainment. Volumetric variation across groups was also explored along with gender differences. Control analyses on the serotoninergic (5-HT), dopaminergic (DA) and cholinergic (Ach) systems were contrasted with the noradrenergic (NA) hypothesis. The antithetic relationships were also tested across the neuromodulatory subcortical systems. Results supported by Bayesian modelling showed that LC volume disproportionately predicted higher attentional performance as well as biological brain maintenance across the three groups. These findings lend support to the role of the noradrenergic system as a key mediator underpinning the neuropsychology of reserve, and they suggest that early prevention strategies focused on the noradrenergic system (e.g., cognitive-attentive training, physical exercise, pharmacological and dietary interventions) may yield important clinical benefits to mitigate cognitive impairment with age and disease.
PUBLISHED
Keywords: noradrenergic theory of Cognitive Reserve; noradrenergic system; Voxel based morphometry; Visual attention; Reserve; Normal aging; Neuroimaging; Mild cognitive impairment; Locus coeruleus; Alzheimer’s disease; Brain age; Ageing